2019
DOI: 10.1371/journal.pone.0222208
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigation and management of bloody diarrhea among children in India

Abstract: BackgroundThe evidence on the factors associated with childhood bloody diarrhea in developing countries in general and India, in particular, is somewhat limited. Our study, therefore, examines—the prevalence of bloody diarrhea; the magnitude of treatment of bloody diarrhea (use of both oral rehydration and antibiotics (pills, syrups, and injections)); and several other associated factors with bloody diarrhea in the youngest children under five years in the Indian context.MethodsWe used data from the National F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
4
12
0
Order By: Relevance
“…Children who were large or average size at birth were less likely to experience diarrhea compared with children who were very small size at birth. This finding is also consistent with the studies from sub-Saharan Africa 15 and India, 60 where the size of the child at birth played an important role in child health and diarrheal morbidity.…”
Section: Discussionsupporting
confidence: 92%
“…Children who were large or average size at birth were less likely to experience diarrhea compared with children who were very small size at birth. This finding is also consistent with the studies from sub-Saharan Africa 15 and India, 60 where the size of the child at birth played an important role in child health and diarrheal morbidity.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study contradict the findings of other previous studies. 41 , 42 A possible reason for these findings could be that some practices or frameworks in the Islamic religion increase children whose mothers practice Islam compared to those who practice Christianity. 41 , 43 Another plausible reason for these findings could be that mothers’ exposure to mass media no more reduces their children’s chances of having diarrhea disease.…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 43 Another plausible reason for these findings could be that mothers’ exposure to mass media no more reduces their children’s chances of having diarrhea disease. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the present study showed the association between religious beliefs and childhood diarrhea [ 34 , 49 , 50 ]. This finding is comparable with previous studies in India [ 34 , 49 ], Kenya, Nigeria, and Niger [ 50 ] that showed the association between religion and healthcare seeking behavior for childhood diarrhea.…”
Section: Discussionmentioning
confidence: 73%